2013
DOI: 10.1186/1749-8090-8-208
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for endotracheal re-intubation following coronary artery bypass grafting

Abstract: BackgroundEndotracheal re-intubation following coronary artery bypass grafting (CABG) is often associated with significant morbidity and mortality. However, few reports have focused on the independent risk factors for re-intubation following CABG. This study aimed to evaluate the independent risk factors for re-intubation following CABG.MethodsThe pre-, intra-, and post-operative materials in patients who had selective and isolated CABG performed on them from January 2004 to July 2012 in our hospital were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Jian et al [16] retrospectively analyzed their data about reintubation for ARF after coronary artery bypass grafting (CABG) over an 8-year period. The incidence of reintubation was 7.8%; reintubation occurred most commonly on the second day after extubation; cardiogenic pulmonary edema and hypoxemia due to pulmonary disease (particularly atelectasis) were the most common causes.…”
Section: Introductionmentioning
confidence: 99%
“…Jian et al [16] retrospectively analyzed their data about reintubation for ARF after coronary artery bypass grafting (CABG) over an 8-year period. The incidence of reintubation was 7.8%; reintubation occurred most commonly on the second day after extubation; cardiogenic pulmonary edema and hypoxemia due to pulmonary disease (particularly atelectasis) were the most common causes.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been described for the left ventricle, with the maximal incidence of pulmonary oedema leading to reintubation occurring on postoperative day 2. 31 Elevated venous pressures could increase the risk of surgical site bleeding. 32 This would contribute to the strong association between portal flow pulsatility after CPB separation with bleeding and reintervention.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study [ 29 ] on surgical ICUs reported that an elevated BUN level (> 8.2 mmol/L) was an independent risk factor for reintubation (OR: 3.66; 95% CI: 1.97–6.80) in patients with a median BMI of 26.9 (no reintubation group; n = 699) and with a median BMI of 26.2 (reintubation group; n = 65). Another study [ 30 ] reported that acute kidney injury (OR: 2.98; 95% CI: 2.13–4.02) was associated with reintubation after coronary artery bypass grafting surgery. Overall, renal failure can be a risk factor of extubation failure in overweight patients and other populations.…”
Section: Discussionmentioning
confidence: 99%